Fake profile detection in social media using image processing and machine learning - Sen, Shuva; Islam, Mohammad Intisarul; Azim, Samiha Sofrana; Norin, Fatema Akhtar; Shuha, Samiha Tasnim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.